Circadian and ultradian cardiovascular rhythmicity in obese children - Saner, Christoph; Simonetti, Giacomo D.; Wühl, Elke; Mullis, Primus E.; Janner, Marco (European journal of pediatrics, 2016)
Altered circadian and ultradian blood pressure (BP) and heart rate (HR) rhythmicity have been described in diseases with increased cardiovascular risk. We analyzed cardiovascular rhythmicity in obese children. BP and HR rhythmicity was assessed with Fourier analysis from 24-h ambulatory BP measurements in 75 obese children and compared with an age- and gender-matched, lean healthy reference group of 150 subjects. Multivariate regression analysis was applied to identify significant independent factors explaining variability of rhythmicity. Prevalence of 24- and 6-h BP rhythmicity in the obese group was lower (p = 0.03 and p = 0.02), whereas the prevalence of HR rhythmicity was comparable in both groups. Excluding hypertensive participants, the results remained similar. Twenty-four-hour BP and HR acrophase were delayed in obese children (p = 0.004, p < 0.0001), 24-h BP amplitude did not differ (p = 0.07), and 24-h HR amplitude was blunted (p = < 0.0001). BP Mesor in the obese group was higher (p = 0.02); HR Mesor did not differ (p = 0.1). Multivariate regression analysis failed to identify a single anthropometric or blood pressure parameter explaining the variability of BP and HR rhythmicity.